Larangan Perkawinan Sesuku Pada Masyarakat Adat Suku Domo di Desa Rumbio Kabupaten Kampar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Ethnic marriage is a relationship of association and marriage or marriage between a man and a woman who is still in the same ethnic relationship. There are three systems of traditional marriage, The background of this research examines that tribal marriage for the domo tribe community is a customary prohibition that must be obeyed by the indigenous community. However, in fact, the swiftness of the era of globalization has destroyed the cultural values of the domo tribe, which in the end, there has been a violation of the prohibition of inter-ethnic marriage. Violation of this prohibition has legal implications, namely that the offender is given very heavy sanctions and is not allowed to marry in the village where he lives. The purpose of this study was to determine the factors causing the prohibition of tribal marriages in the indigenous peoples of the domo tribe in Rumbio Village, Kampar Regency, and to determine the sanctions imposed on violations of the prohibition of tribal marriages in the domo tribal community in Rumbio Village, Kampar Regency.This type of research can be classified in the type of sociological research, because in this study the author directly conducts research at the location or place under study in order to provide a complete and clear picture of the problem under study. This research was conducted in Rumbio Village, Kampar Regency, while the population and sample are all parties related to the problems studied in this study, the data sources used, primary data, secondary data, and tertiary data, data collection techniques in this study are observations. , interviews and literature study.From the research, there are three main points that can be concluded. First, the factors that cause the prohibition of tribal marriages are the existence of blood relations, unqualified offspring, narrow associations, can break the ties of brotherhood, break lineages, the existence of the kowi oath, and the domo tribe that is not divided. Second, the sanctions for violations of the prohibition of inter-ethnic marriage are being ostracized in the community, evicted from the village and expelled from the five koto nagari, being fined with an ox, being fined with rice / rice as much as one Rangkiang / Lumbung Padi. Author's suggestion, first, to prevent the occurrence of inter-ethnic marriages, Ninik Mamak in Rumbio Village, Kampar Regency, is able to provide socialization to the community, especially regarding customary regulations regarding the prohibition of inter-ethnic marriages, thereby creating awareness and compliance so that no more people consider the provisions customs regarding the prohibition of tribal marriages are no longer in accordance with the times or violate human rights. Second, parents should be able to heal the spirit of education for the younger generation, which in this case must be started from parents because they have an important role in the education and association of children in society so that they have more extensive knowledge so that there is no wrong or half-understanding.Keywords: Ethnic marriage, Kampar customs, Prohibition of Customary Marriages.